PENGARUH BRAND IMAGE, CELEBRITY ENDORSEMENT DAN HARGA TERHADAP KEPUTUSAN PEMBELIAN RAKET MEREK YONEX : STUDI PADA KONSUMEN RAKET YONEX DI KOTA MEDAN - Nur Putri Handayani; Satria Mirsya Affandy Nasution (Fisarrearch, 2023)
The purpose of this research is to find out whether there is an influence of brand image, celebrity endorsement and price on the decision to purchase Yonex brand rackets.This type of research is quantitative with an associative approach. The population in this study were people who had purchased and used Yonex brand rackets. The research sample was determined using a purposive sampling technique with a sample size of 100 people. The data collection technique in this research uses a questionnaire. The data analysis technique in this research uses the classic assumption test, multiple linear regression analysis, hypothesis testing (t test and f test) and coefficient of determination. Data processing in this research used the SPSS (statistical package for the social sciences) software program version 21.In this research, the results showed that partially and simultaneously the variables brand image, celebrity endorsement and price had a positive and significant effect on the decision to purchase Yonex brand rackets. So the hypothesis is accepted.Keywords ; Brand Image, Celebrity Endorsement, Price and Purchase Decision